1979
DOI: 10.1088/0022-3727/12/8/003
|View full text |Cite
|
Sign up to set email alerts
|

Radiation field induced perturbations in CO2laser plasmas. I. Current and pressure fluctuations

Abstract: Changes in the 10.6 mu m CO2 laser resonant radiation field cause gas number density changes in the irradiated volume by V-T energy exchange and gas heating. This primary pressure fluctuation ( approximately 0.5%) causes a change in the mean energy exchange per electron-molecule collision dX/X and a change in the electron mean free path lambda and hence the discharge current. The current fluctuation di/i ( approximately 1 to >10%) can be eliminated with a constant-current power supply with a sufficiently rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The opto-galvanic effect (OGE) in C02 laser gas mixtures has required detailed examination because of its utilisation in laser frequency and power stabilisation. In the previous paper (Moffatt and Smith 1984, henceforth referred to as MS) we have presented a detailed analysis of the effect based on the discharge cooling mechanism established by Smith and Brooks (1979) and have found excellent agreement between the theory and experimental results. Alternatively Nowicki and Pienkowski (1982, henceforth referred to as NP) have advanced a substantially different theory of the OGE based on radiation field perturbation of the multi-step ionisation of the N2 component usually present in C02-N2-He laser gas mixtures.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The opto-galvanic effect (OGE) in C02 laser gas mixtures has required detailed examination because of its utilisation in laser frequency and power stabilisation. In the previous paper (Moffatt and Smith 1984, henceforth referred to as MS) we have presented a detailed analysis of the effect based on the discharge cooling mechanism established by Smith and Brooks (1979) and have found excellent agreement between the theory and experimental results. Alternatively Nowicki and Pienkowski (1982, henceforth referred to as NP) have advanced a substantially different theory of the OGE based on radiation field perturbation of the multi-step ionisation of the N2 component usually present in C02-N2-He laser gas mixtures.…”
Section: Introductionmentioning
confidence: 65%
“…In a previous paper (Smith and Brooks 1979) we have shown that there is a large OGE in a pure CO2 discharge as well as in C02-N2-He mixtures, but of opposite polarity because the CO2 is usually in a state of absorption rather than emission. Figure 5 shows results for the variation of the normalised effect AV/ (VP,,,) with current for a laser mixture including nitrogen (squares) and a similar mixture excluding nitrogen but including carbon monoxide (circles).…”
Section: The Amplitude Of the Ogementioning
confidence: 90%
“…see Smith and Brooks 1979) then any change of electron energy loss is primarily due to a change in the number of collisions which occur. The number of collisions is directly proportional to the number density of all the possible collision partners (n).…”
Section: Power Perturbation Theory For Coz Laser Oscillatorsmentioning
confidence: 99%
“…It has been previously shown (Smith and Brooks 1979) that if the power supply is operated in a constant voltage mode, analysis of the discharge perturbations will be considerably complicated for two reasons. First the constant voltage is at the power supply terminals, and current amplitude changes produced by the power supply to compensate for discharge impedance changes will produce a variation of potential difference across the series ballast resistor and hence the potential difference across the laser tube itself will not be constant.…”
Section: The Laser Systemmentioning
confidence: 99%
“…Upon the first application of lasers in optogalvanic (OG) studies [1], the laser optogalvanic effect found widespread application in various fields [2][3][4][5][6][7][8][9][10][11]. As regards CO 2 lasers, all microscopic laser-plasma processes occurring in such active mediums have been well studied [12][13][14][15], and various OG signal detection methods in DC and RF discharge tubes have been discussed in details [16][17][18][19][20][21]. Moreover, both the dependence of the OG signal phase and amplitude on the laser modulation frequency [22][23][24] and the temporal behavior of signal shapes [25][26][27] have been theoretically and experimentally studied in many previous works.…”
mentioning
confidence: 99%